Impact of weld restraint on the development of distortion and stress during the electron beam welding of a low-alloy steel subject to solid state phase transformation. (15th April 2021) - Sun, Y.L.; Vasileiou, A.N.; Pickering, E.J.; Collins, J.; Obasi, G.; Akrivos, V.; Smith, M.C.
Highlights: Thermal-metallurgical-mechanical model for electron beam (EB) welding in SA508 Gr.4N low-alloy steel plate has been developed and validated. Inter-part gapping occurs when EB weld centre plane is not restrained before welding, but the gapping distortion can be mitigated by tack-weld restraint. High tensile stress is induced at stop-end tack weld during welding, which can be effectively reduced by increasing tack-weld extent. Tack-weld restraint hardly affects final weld residual stress which exhibits steep gradient across heat affected zone (HAZ) boundary. Weld-induced martensitic transformation promotes compression and suppresses tension in EB weld and HAZ, and peak tensile residual stress is concentrated in base material immediately outside HAZ. Abstract: Electron beam (EB) welding has a low tolerance to inter-part gapping distortion and can generate complicated stresses, which pose challenges to weld quality and integrity. This study investigates welding distortion and stresses in an EB welded plate made from SA508 Grade 4N low-alloy steel. A thermal-metallurgical-mechanical model was developed to predict the temperature, micro-constituents, hardness, distortion and stresses in the EB weldment; the predictions are in good agreement with experimental results. Different restraint conditions on the weld plane were modelled to examine their effects on distortion and stresses. If welding is performed with no restraint, inter-part gapping develops ahead of the beam position that could exceed the tolerance for a sound weld. In contrast, tack welds at the plate ends significantly reduce this gapping, but induce additional tensile stress at the stop-end tack weld. This stress is particularly high as the beam approaches the tack weld. Increasing the extent of the tack weld reduces the tensile stress, while increasing number of distantly distributed narrow tack welds does not help. A full through-length restraint eliminates the opening gap and minimises the development of tensile stresses ahead of the beam that could potentially break the restraint. The applied restraint on the weld plane has little effect on the final residual stress field, since this field mostly develops during cooling after the EB weld is complete. The weld-induced martensitic transformation suppressed tension or promoted compression in the EB weld and heat affected zone (HAZ). A steep gradient of residual stress exists, with high tensile stress concentrated in a narrow region immediately outside the HAZ. Graphical abstract: Image, graphical abstract